Coexistence effect of UVA absorbers to increase their solubility and stability of supersaturation. (23rd September 2014) - Endo, M.; Mukawa, T.; Sato, N.; Maezawa, D.; Ohtsu, Y.; Kuroda, A.; Wakabayashi, M.; Asakura, K.
Synopsis: Objective: Sunscreens containing UVA absorbers in high concentrations are expected to be developed, since recent studies have suggested the possibility of involvement of UVA ray in skin cancer and early skin aging. Solubility and stability of supersaturation of UVA absorbers in UVB absorber were determined in the absence and the presence of cosmetic oil. Coexistence effect of UVA absorbers was analyzed to dissolve them in high concentrations. Methods: Two UVA absorbers, diethylamino hydroxybenzoyl hexyl benzoate (DHHB) and butyl methoxydibenzoylmethane (BMDM), a UVB absorber, 2‐ethylhexyl methoxycinnamate (EHMC), and a cosmetic oil, 2‐ethylhexyl ester of oligomer of hydroxystearic acid (EH‐O‐HSA), were used. Their solutions were prepared at 80°C and cooled to 5°C. The solid DHHB and/or BMDM were added to it, and the time evolution of concentrations of the UVA absorbers in the solution phase was monitored. Results: At the saturation in the absence of EH‐O‐HSA at 5°C, weight ratio of DHHB and BMDM to EHMC was 0.39/1.00 and 0.22/1.00, respectively. Addition of EH‐O‐HSA slightly changed the solubility of DHHB and BMDM. When the weight ratio of EH‐O‐HSA to EHMC was 0.20/1.00, weight ratio of DHHB and BMDM to EHMC was 0.35/1.00 and 0.25/1.00, respectively at the saturation at 5°C. In the presence of EH‐O‐HSA, a strong coexistence effect of DHHB and BMDM was found on their solubility. A thermodynamically stable saturated solution at 5°C having the composition that DHHB: BMDM: EHMC: EH‐O‐HSA = 0.47: 0.46: 1.00: 0.20 was obtained by the simultaneous addition of solid DHHB and BMDM into the initial solution. Conclusion: The solution type composite having the highest concentrations of DHHB and BMDM prepared in this study exhibited critical wavelength at 368 nm that was just below the border for sunscreens being qualified as 'Broad Spectrum' protection under the new rule launched by US FDA.